Coexistence for Whom? - Pooley, Simon (Frontiers in Conservation Science, 2021)
This perspective essay considers ethical and conceptual questions around who coexistence is for, who it affects, and who is to make it happen. It first considers some approaches to thinking about human-wildlife coexistence, debates on the utility of the concept and reasons for its current emergence into the mainstream. It next outlines the preliminary conception of the concept underlying this essay. The discussion considers challenges for a narrow conservation-oriented framing of human-wildlife coexistence, and offers insights from the literatures on stewardship and relational values for thinking about these.